ENSURING CONFIDENCE IN LABORATORY DATA: A REVIEW OF QUALITY CONTROL AND ASSURANCE PRACTICES - Belgaith Otman Belgaith Alsefri, Ali Ahmedali Alsayed, Ghalib Ali Ahmed Almaqadi, Mohammed Abduh Jaber Alhelaly, Noori Mabred Noori Alsayed, Mousa Mohmad Abdo Alhassni, Abubakr Ali Bilghith Alsohbi, Ahmed Belqasem Nasser Alsolbi, ,; Bahni Mohamaad Ibrahim Algoozy, Safiah Hassan Alasiri, Mssawed Ahmed Mohmed Darrag, Rayid Mater Mohammed Alahmdi, Mohammed Tuhaymir Muawwadh Alanmi, Mohammed Abdullah Meerbaba Qasem, (Chelonian Research Foundation, 2022)
Ensuring accurate and dependable test findings is of utmost importance in clinical labs, making quality improvement essential. Given the growing recognition of the negative impact that mistakes in laboratory procedures may have on patient results, it is crucial to underline the ongoing need for enhancing laboratory services. A systematic literature review was performed on PubMed and the Web of Science Core Collection from October to February 2021 to assess the scientific rigor of clinical laboratory quality improvement studies. Only peer-reviewed articles written in English that satisfied the criteria for quality improvement were considered. The studies were examined based on the methodologies and treatments used for quality improvement and control, such as training, education, task force, and observation. The findings indicated a consistent enhancement in the quality of improvement papers in the clinical laboratory sector. Specifically, the average score of QI-MQCS increased from 2.5 (1981-2000) to 6.8 (2001-2020). Nevertheless, there is an opportunity to develop a systematic approach for evaluating the quality of clinical laboratory literature and enhancing accrediting processes in the field. Keywords: performance assessment, comprehensive quality management, analytical quality, QI-MQCS